AN EXPLORATORY STUDY TO IDENTIFY TEACHING STYLES IN SAUDI ARABIA BASED ON THREE LEARNING THEORIES - Alqurashi, Mohammed (PEOPLE: International Journal of Social Sciences, 2018)
The purpose of this quantitative study was to investigate Saudi teachers’ philosophy in teaching based on three major learning theories (behaviorism, cognitivism, and constructivism). Also, it showed the different between gender (male, female), and teachers’ experiences in teaching (1-5, 6-10, 11-15, 16-20, more than 20 years), and level of teaching (Elementary, Middle, and High) school in the preferred teaching philosophy. The result showed that Saudis’ teacher proffered using cognitivism philosophy more than constructivism philosophy and behaviorism philosophy. Although the male teacher had preferred behaviorism school more than female teachers, the female teachers had preferred cognitivism and constructivism schools more than male teachers. Also, the teachers who had more experience preferred cognitivism and constructivism schools more than behaviorism school.